Perubahan Sosial Budaya dan Dampaknya terhadap Identitas Masyarakat - Debby Widitya; Usiono (JURNAL ILMIAH NUSANTARA, 2025)
Social and cultural change is an inevitable phenomenon in an evolving society. In the context of Indonesia, this transformation is often driven by factors such as globalization, technological advancements, and cross-cultural interactions. This study aims to analyze how social and cultural changes impact community identity, both positively and negatively. Using a qualitative approach, the research collected data through interviews and observations of various community groups across several regions. The findings reveal that while social and cultural changes can enrich community identity by introducing new values, they also pose risks of losing valuable local traditions and identity. Therefore, it is crucial for communities to balance embracing change with preserving local culture to maintain the diversity and richness of national identity.